Optical properties of CdTe thin film obtained by high-frequency magnetron sputtering method - Kashuba, Andrei I.; Andriyevsky, Bogdan V.; Ilchuk, Hrigorii A.; Piasecki, Mikhal; Semkiv, Igor’ V.; Petrus, Roman Yu. (Journal of the Belarusian State University. Physics, 2021)
Cadmium telluride (CdTe) thin films relate to AII BVI compounds and show semiconductor behaviour. They present an important research field because of their wide application in various optoelectronic devices. CdTe-based solar cells attract attention since CdTe is characterised by the direct energy bandgap Eg and high absorbance, which makes it an excellent light-absorbing layer of solar cells. Material evaporation in vacuum by using the high-frequency magnetron sputtering method is one of the most advantageous methods for obtaining uniform films. The present work is dedicated to the investigation of the optical properties of CdTe thin film, which is produced on quarts substrate by the high-frequency magnetro sputtering method. The optical transmission, reflectivity, and μ-Raman spectra of the CdTe thin film have been determined. Linearity of the spectral dependence of the coefficient of optical absorption α of CdTe thin film in the coordinates (αhν)2 vs hν indicates for the direct character of optical transitions corresponding to the long-wavelength edge of fundamental absorption. The optical bandgap of the studied CdTe thin film is found to be Eg = 1.53 eV. The peaks of the experimental m-Raman spectra at 121; 139; 142; 167 and 331 cm–1 are attributed to the phonons in crystalline CdTe and Te.